The environmental and legal impacts of the textile industry on fashion law - De Vettori Dorador, Denissela (2022)
Currently, the excessive production of textile products and the rise of the fast fashion model causes a continuous but constant deterioration of the environment. For this reason, this article intends to analyze the impacts of the textile industry from an environmental perspective and the defense of people's rights. To do this, we will address the difference between two models of the fashion industry: fast fashion, and the alternative model of slow fashion. Finally, the role that Fashion Law should have in the design and elaboration of the necessary regulation for the protection of the environment and the adoption of sustainable fashion models will be considered.